Faktor- Faktor yang Mempengaruhi Perilaku Seks Pranikah pada Remaja Berdasarkan Teori Health Belief Model (HBM): Studi Literatur 2013-2025 - Syifa Aprilia Azzahra; Luqman Effendi (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Premarital sexual behavior in adolescents is a public health issue influenced by various individual, social, and environmental factors. Changes in social norms, technological advancements, and limited reproductive health knowledge make adolescents a group vulnerable to risky sexual behavior. This study aims to examine the factors influencing premarital sexual behavior among adolescents based on the Health Belief Model (HBM) approach. The method used is a Systematic Literature Review (SLR), review national and international scientific articles published between 2013 and 2025. Data sources were abtained from Google Scholar and ScienceDirect, with inclusion criteria including articles in Indonesia and English, open access, full text, and relevant to HBM components. The study result indicate that factors such as perceived barriers, self-efficacy, and the quality of information play an important role in shaping adolescent sexual behavior. Low knowledge and limited perception oh the negative impacts of premarital sex increase the risk of engaging in risky sexual behavior. In addition, health promotion interventions based on the Health Belief Model (HBM) have been proven effective in improving knowledge, attitudes, and preventive behaviors regarding premarital sex among adolescents. Therefore, the HBM approach is recommended as a basis for developing comprehensive and sustainable adolescent reproductive health education and promotion programs.